Education of making natural hand sanitizers to the community of Haulasi Village, North Central Timor Regency - Adu, Risna Erni Yati; Tnunay, Ite Morina Yostianti; Benu, Didi Prasetyo; Makin, Florian M. P. R.; Hanas, Dicky; Kamaluddin (Talenta Publisher, 2020)
The availability of hand sanitizers, which is one of the Covid-19 prevention media, is becoming scarce and expensive due to their increasing use, making them difficult to reach by the public. Therefore we need another source of active ingredients that more easily obtained, available in abundant quantities and more economically to be used as a substtitute for hand sanitizer raw materials by the public. Potential alternantive material to be used as raw material for hand sanitizer is betel leaves, however, public knowledge about the benefits and methods of processing betel leaves into hand sanitizer is very limited. Therefore, education about the use of betel leaves into natural hand sanitizer products to rural communitties needs to be done to increase people’s insight about making natural hand sanitizer and increase public awareness in maintaining hygiene by providing and using similar products.